Achieving Quality and Effectiveness in Dementia Using Crisis Teams (AQUEDUCT): a randomised controlled trial evaluating the impact of a best practice Resource Kit used by teams managing crisis in dementia - M. Orrell; L. O’Raw; D. M. Coleston; M. Opazo Breton; B. Guo; T. Dening; J. Hoe; B. Lloyd-Evans; E. Moniz-Cook; F. Poland; M. Redley; A. Worden; et al. (Nature Communications)
Abstract People with dementia frequently experience mental health crisis requiring psychiatric hospital admission. In the UK, Teams Managing Crisis in Dementia (TMCDs) vary in structure and practice due to the absence of a standardized model. A pragmatic, randomised controlled trial (RCT) was designed to evaluate the AQUEDUCT Best Practice Tool and online Resource Kit (RK). Twenty-three TMCDs across England were randomised 1:1 To receive the RK plus usual care (intervention) or usual care alone (control) ( www.isrctn.com/ISRCTN42855694 ). The primary outcome was the number of psychiatric hospital admissions for people with dementia at the primary endpoint of six months. Secondary outcomes included TMCD staff mental health (GHQ-12), psychological flexibility (WAAQ), and work engagement (UWES); and for people with dementia and carers, service satisfaction (CSQ-8) and mental wellbeing (GHQ-12). There was no significant difference in number of psychiatric admissions between groups (incident rate ratio: 0.74; 95% CI: 0.37-1.48; p = 0.397) and the primary endpoint was met. No significant differences were found for the secondary outcomes across staff or service user groups. Fidelity to the intervention varied; five TMCDs met or exceeded implementation criteria, while others reported structural barriers. Limited engagement was attributed to the absence of a learning collaborative and pandemic-related service pressures. Although the RK was valued by staff for guiding quality improvement, it did not significantly reduce hospital admissions or improve secondary outcomes. Future studies should prioritise implementation support and explore systemic barriers to service improvement in dementia crisis care.